TREN KESEHATAN MENTAL DAN KAITANNYA DENGAN ETOS KERJA GENERASI Z DI ERA DIGITAL - Uno, Devi Oktavia; Wahyudi, Fatimah Az Zahra; Fiernaningsih , Nilawati; Utami, Rachma Bhakti (Business Administration Department - Universitas Katolik Parahyangan, 2023)
Generation Z, the latest working generation born between 1995 and 2012, has grown amidst the advancement of the digital technology era. As a generation that coexists with technology and benefits from easy access to information, Generation Z demonstrates a heightened sensitivity to various forms of information available on social media, including the trending awareness of the importance of mental health. The increasing trend of mental health awareness within Generation Z significantly influences their work ethic. This research aims to assess the extent of the impact of mental health trends on the work ethic behavior of Generation Z in the professional world. The research employs a qualitative descriptive approach utilizing Systematic Literature Review methodology. The findings of this study reveal the substantial influence of mental health trends on the work ethic of Generation Z. Moreover, the outcomes contribute to a better understanding of how mental health awareness trends shape the work behavior of this generation in the workplace.